The Role of ATC Simulation Training in Enhancing Controllers Competence for Abnormal Situations at JATSC - Ridwan Andi Prasetiyo; Martha Saulina; Ichyu Machmiyana (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Aviation safety is a top priority in the complex and high-risk aviation industry. Air Traffic Controllers (ATCs) are vital in maintaining safety by managing air traffic and responding effectively to abnormal situations such as adverse weather, equipment failure, or communication disruptions. This study aims to analyze the role of ATC simulation training in enhancing ATC competence, particularly in managing abnormal situations at the Jakarta Air Traffic Service Centre (JATSC). A quantitative descriptive-correlational approach was employed, involving 81 ATCs who had completed simulator training within the past two years. Data were gathered through Likert-scale questionnaires, interviews, observations, and documentation, and analyzed using Pearson correlation and multiple linear regression tests. The results indicate that simulation training significantly contributes to improving ATCs’ technical, cognitive, and affective competencies, including decision-making, situational awareness, operational communication, and stress management. These findings highlight the importance of simulation-based learning as an effective method to strengthen ATC readiness and operational performance. The study provides valuable insights for curriculum enhancement at JATSC and serves as a reference for policy formulation aimed at reinforcing aviation safety at the national level